A pilot and feasibility study of a randomized clinical trial testing a self-compassion intervention aimed to increase physical activity behaviour among people with prediabetes - Signore, Alana K.; Jung, Mary E.; Semenchuk, Brittany; Kullman, Sasha M.; Tefft, Olivia; Webber, Sandra; Ferguson, Leah J.; Kowalski, Kent; Fortier, Michelle; McGavock, Jon; Ahmed, Rashid; Orr, Marion; et al. (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Seventy-five per cent of individuals with prediabetes will eventually be diagnosed with type 2 diabetes. Physical activity is a cornerstone in reducing type 2 diabetes risk but can be a challenging behaviour to adopt for those living with prediabetes. Individuals with prediabetes experience difficult emotions associated with being at risk for a chronic disease, which can undermine self-regulation. Self-compassion enhances self-regulation because it mitigates difficult emotions and promotes adaptive coping. We performed a pilot randomized controlled trial to determine the feasibility and acceptability of a self-compassion informed intervention to increase physical activity for persons with prediabetes. Methods This explanatory mixed methods study tested the feasibility and acceptability of a two-arm, randomized, single-blind, actively controlled, 6-week online intervention. Using a 1:1 allocation ratio, participants (identified as people with prediabetes, low physical activity, and low self-compassion) were randomized to a self-compassion (Mage = 60.22 years) or control condition (Mage = 56.13 years). All participants received behaviour change education (e.g. SMART goals, action-coping planning) and either other health knowledge (control condition: e.g. sleep, benefits of water) or self-compassion training (intervention condition: practising mindfulness, writing a letter to themselves offering the same support that they would offer to a friend). The primary outcome was to determine the feasibility and acceptability of the trial. To be considered feasible, our outcomes needed to meet or surpass our pre-determined criteria (e.g. time for group formation: 14–20 participants per month). Feasibility was assessed by examining the recruitment rates, retention, adherence, fidelity, and capacity. Semi-structured interviews were conducted with participants to determine trial acceptability. As a secondary purpose, we examined the means on key study variables (secondary and exploratory variables; see Table 1) at all planned time points (baseline, intervention-end, 6- and 12-week follow-up) to identify if they are suitable to include in the efficacy trial (see Additional Table 3). Results Eighteen participants were screened and randomized to one of two conditions. Retention, instructor fidelity, safety, capacity, adherence to most of the study aspects, and acceptability by participants and facilitators all met the criteria for feasibility. Recruitment rate, process time, and adherence to home practice were below our criteria, and we offer ways to address these shortcomings for the efficacy trial. Conclusion The results from this study suggest that it should be feasible to deliver our intervention while highlighting the alterations to components that may be altered when delivering the efficacy trial. We outline our changes which should improve and enhance the feasibility and acceptability of our planned intervention. Funding for this study was from the Canadian Institutes of Health Research (CIHR). Trial registration ClinicalTrials.gov, NCT04402710 . Registered on 09 April 2020.